Implementasi Kode Etik Keperawatan Sesuai Dengan Undang-Undang Nomor 17 Tahun 2023 Dalam Pelayanan Keperawatan Anak - Hamzah, Alfian Dwi; Kusbiantoro, Dadang; Harmiardillah, Sylvi; Suratmi, Suratmi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
The nursing code of ethics played a crucial role in ensuring that pediatric nursing care adhered to professional, ethical, and legal standards. However, its implementation faced various challenges. This study analyzed the application of the code of ethics in pediatric nursing care based on Law No. 17 of 2023 and the factors influencing its implementation. This research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews with nurses in the pediatric care unit at RSU Muhammadiyah Babat Lamongan, as well as an analysis of the nursing code of ethics and legal regulations. The findings reveal that nurses' understanding of the code of ethics varies, influenced by work experience and training. Five main themes emerged: the relationship between nurses and clients, nursing practice, society, colleagues, and the profession. The alignment of the code of ethics with Law No. 17 of 2023 is evident in several articles, including Articles 44-49, 23(2), 177(1), and 291(1). The primary challenges included ethical conflicts in decision-making, communication with patients' families, and limited resources. Continuous training and clearer hospital policies were necessary to enhance compliance with the code of ethics.